Performance Analysis of TFRC and UDP over Mobile-IP Network with Competing Flows - Ali R, Alhuzali Abed (2010)
This study aimed to conduct a performance analysis of TFRC and UDP over mobile-IP network with competing flows that enables to investigate three major performance metrics such as jitter, throughput, packet loss and packet delay. Two different transport layer protocols have been used in this analysis. As mobility has been the core issue of computing of 21st century, this research aims to contribute to this phenomenon by implementing performance analysis in mobile IP network, where mobile devices (nodes) are moved from access points to access points (AP) in order to exemplify the suitability of TFRC and UDP in wireless networking. Moreover to collect data about crucial performance metrics features. The experiment has been conducted by Network Simulation (NS-2).